Chronic Diseases and Associated Factors among Older Adults in Loja, Ecuador - Patricia Bonilla-Sierra (International Journal of Environmental Research and Public Health, 2020)
(1) Background: This study aimed to explore the symptoms, functional status, and depression in patients with chronic diseases in Loja, Ecuador. (2) Methods: A cross-sectional study was carried out with patients over 60 years old having at least one chronic disease and cared for in healthcare centers of the Health Ministry of Ecuador or living in associated geriatric centers. (3) Results: The sample comprised 283 patients with a mean age of 76.56 (SD 7.76) years. The most prevalent chronic diseases were chronic obstructive pulmonary disease, followed by arterial hypertension and diabetes. Patients with a joint disease had the worst scores for the majority of the symptoms assessed with the Edmonton Scale. Cancer, dementia, and arterial hypertension contributed the most to the dependence levels assessed with the Barthel Index. Dementia contributed the most to the poor performance status evaluated with the Karnofsky Performance Status. Cancer and diabetes contributed the most to depression. Patients with a higher number of chronic diseases reported worse functional status. (4) Conclusions: Targeted interventions to address symptoms, functional status, and depression in patients with chronic diseases are needed.